PERBANDINGAN PENGARUH METODE LATIHAN PLYOMETRICS DOUBLE LEG BOUND, ALTERNATE LEG BOUND DAN INCRIMENTAL VERTICAL HOP TERHADAP PRESTASI LOMPAT JANGKIT DITINJAU DARI RATIO TINGGI BADAN, PANJANG TUNGKAI - RONNI SURYO NABITO (Universitas Tunas Pembangunan, 2014)
The aim of this research is to know : (1) the differences of the method effect exercise of plyometrics double leg bound, alternate leg bound and incremental vertical hop to the achievement of bob up and down hop, (2) the differences achievement of bob up and down hop between the boy students who have high body ratio and the length of leg. Category â€œhighâ€, â€œmiddleâ€, and â€œlowâ€. The method which is used in this research is experiment method with factorial plan 3x3. The sample of this research is the boy students of health and sport education program FKIP UTP Surakarta. The total number is go students. The variable of this research is consist of two free variable and one bound variable. The free variable in this research is : (1) the method exercise of plyometrics as manipulative variable with three levels. They are double leg bound, alternate leg bound and incremental verticalÂ hop, (2) the high body ratio and the length of leg as attributive variable with three levels. They are high, middle, and low. The technic of collecting data is technic test and measurement. The experiment is three times in a week, every meeting 2x50 minutes for 18 times meeting. The experiment is done at the area of health and sport education program, FKIP, UTP Surakarta. The Technic of Analysis Data is two ways of variancy analysis and advanced test using t-test method LSD (Least Significant Difference) to the level of signification 5% (Î± = 0,05). Computation in the variancy analysis using the help of the minitab 16 statistic program. The result of the study is : (1) there is differences the plyometrics exercise method to the achievement double leg bound giving the best effect to the achievement of bob up and down hop. (2) there is achievement of bob up and down hop between the students who have high body ratio and the length of leg with the category high, middle and low. F obs = 15,55, P = 0,000. The students group who have the high body ratio and the length of leg with the low category have the best achievement compared with the other groups (high and middle category). (3) there is interaction between plyometrics exercise method and high body ratio and the length of leg. F obs = 4,31, P = 0,0003. The students group who have the high body ratio and the length of with low category in plyometrics exercise method double leg bound have the best achievement rate 10,99. Â